2011
DOI: 10.3109/07420528.2011.613136
|View full text |Cite
|
Sign up to set email alerts
|

When Does Stress End? Evidence of a Prolonged Stress Reaction in Shiftworking Truck Drivers

Abstract: This study aimed to analyze individual cortisol levels in relation to work conditions, sleep, and health parameters among truck drivers working day shifts (n = 21) compared to those working irregular shifts (n = 21). A total of 42 male truck drivers (39.8 ± 6.2 yrs) completed questionnaires about sociodemographics, job content, work environment, health, and lifestyle. Rest-activity profiles were measured using actigraphy, and cardiovascular blood parameters were collected. Salivary cortisol samples were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
(46 reference statements)
2
32
0
1
Order By: Relevance
“…Cortisol peaks half an hout after waking, and the stronger the increase (CAR), the heavier the chronic perceived stress. For logistic reasons CAR could not be registered in this series, only the 30 minutes peak, however both are often related, and might be correlated with metabolic abnormalities (27) . Despite the lack of CAR estimates in the current protocol, the biochemical stress model was preferred for the purposes of objectivity and reproducibility, as psychological stress and burn out have been assessed by a heterogeneous array of questionnaires, scales, instruments and inventories (11,17,22,23,31) .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Cortisol peaks half an hout after waking, and the stronger the increase (CAR), the heavier the chronic perceived stress. For logistic reasons CAR could not be registered in this series, only the 30 minutes peak, however both are often related, and might be correlated with metabolic abnormalities (27) . Despite the lack of CAR estimates in the current protocol, the biochemical stress model was preferred for the purposes of objectivity and reproducibility, as psychological stress and burn out have been assessed by a heterogeneous array of questionnaires, scales, instruments and inventories (11,17,22,23,31) .…”
Section: Discussionmentioning
confidence: 89%
“…Only morning cortisol was registered, not circadian profile, or specific stimulation and suppression maneuvers (6,8,24,27) . Urinary, salivary or hair cortisol were not monitored, nor epinephrine, norepinephrine, cytokines or other biomolecules (6,10,19,26) .…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the prevalence of excessive sleepiness is known to be higher in shiftworkers than in non-shiftworkers (Drake et al, 2004;Garbarino et al, 2002;Pallesen et al, 2007). Moreover, it has been reported that their irregular working hours might increase their vulnerability to the development of insomnia symptoms (Drake et al, 2004;Garbarino et al, 2002;Lin et al, 2012), elevated stress response (Ulhoa et al, 2011), decreased mental health (Lin et al, 2012), and depressed mood (Driesen et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…All these factors contribute to increased sick leave [14] and an increased turnover of phone operators owing to their premature departure to other less stressful professions [15]. Objective measurements of stress are therefore needed to develop evaluable preventive strategies of stress management [16,17,18]. To identify stress at a biological level, cortisol is the historical biomarker which can now be assessed easily and pain-free from saliva [19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%